The Effect Of Variation Training On The Underwear Passing Skills Of Extracurricular Volleyball Players At State Senior High School 2 Bengkulu City - Rika Putriani; Megi Personi; Dolly Apriansyah (Journal of Education, 2026)
This study aims to determine: To determine the Effect of Variation Training on Underhand Passing Skills in Volleyball Players of SMAN 2 Bengkulu City. This type of research is experimental research. The sample of this study was all extracurricular volleyball players of SMAN 2 Bengkulu City, totaling 16 people. This can be seen from the increase in volleyball passing skills through the initial test and the final test. The initial test (pre-test) the highest score was 15 and the lowest score was 9, the average was 11.69 The final test (post-test) the highest score was 20 the lowest score was 14, the average was 17.31. The instrument used in this study was the volleyball underhand passing ability Based on the pre-test and post-test data of the underhand passing ability of the extracurricular volleyball game of SMAN 2 Bengkulu City, the results of the normality test were obtained, all of the data were normally distributed. Furthermore, the t-test results showed tcount: 7.305 > ttable: 1.753.